Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Genetic structure of Sydney Cockle Anadara trapezia: Implications for stock assessment and restoration of extirpated populations - Matthew D. Taylor; Matthew Freeman; Rowan C. Chick; Laura Parker; Wayne O’Connor; Sankar Subramanian (Fisheries Research, 2026)

Investigation of shell banding in an arcid cockle alongside trace-element concentrations to evaluate potential suitability for age estimation - Patrick Reis-Santos; Rhiannon A. Van Eck; Charlotte Gauthier; Joseph B. Widdrington; Rowan C. Chick; Bronwyn M. Gillanders; Matthew D. Taylor (Fisheries Research, 2025)

Identifying capacity limitations and training needs using a stock assessment game - André E. Punt; Catherine M. Dichmont; Natalie A. Dowling; Roy A. Deng; Sean Pascoe; Ingrid van Putten; Pia Bessell-Browne; Paul Burch; Owen Burnell; Rowan C. Chick; Simon de Lestang; Ainslie Denham; et al. (Fisheries Research, 2025)

Aging of the sea urchin Centrostephanus rodgersii using demi-pyramid microstructure - Craig Blount; Duncan G. Worthington; Maria Byrne; Rowan C. Chick; Neil L. Andrew (Fisheries Research, 2024)

Utility of a modified lightweight recreational scallop dredge for surveys of estuarine ark clams (cockles) - Matthew D. Taylor; Rowan C. Chick (Fisheries Research, 2024)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

The FishPath approach for fisheries management in a data‐ and capacity‐limited world - Natalie A. Dowling; Jono R. Wilson; Jason M. Cope; Dawn T. Dougherty; Serena Lomonico; Carmen Revenga; Brian J. Snouffer; Natalio Godoy Salinas; Felipe Torres‐Cañete; Rowan C. Chick; Ashley M. Fowler; Ana M. Parma (Fish and Fisheries, 2023)
Successful fisheries management systems tend to be underpinned by harvest strategies, specifying formally agreed data collection systems, assessment approaches and management measures used to regulate fishing pressure. While harvest strategies can be effective even in data‐ and capacity‐limited (DCL) situations, their development remains challenging in such contexts. We present a process and decision‐support tool, FishPath, to guide the identification of suitable harvest strategy component options given often debilitating conditions: (i) resource limitations and lack of technical management capacity; (ii) ‘uniqueness’ of DCL fisheries; (iii) the concept of harvest strategies is unfamiliar to managers and scientists, and the universe of options is hard to navigate; and (iv) the lack of an effective participatory process to identify solutions tailored to local contexts. These conditions can lead to either management paralysis or generic solutions that may be poor fits to specific conditions. The FishPath Tool uses a diagnostic questionnaire that elicits the key characteristics and specific circumstances of a fishery. It compares these with the requirements of alternative options from an inventory of possible harvest strategy components, identifies where these requirements are met and provides customised, transparent guidance on the appropriateness of component options of a harvest strategy, specific to the fishery of interest and its governance context. The FishPath Process is a facilitated multi‐stakeholder, participatory engagement process aimed to set fisheries on the path to develop a harvest strategy. The FishPath Process and Tool combine to ensure a bottom‐up, documented, transparent, replicable and efficient process.

The stock assessment theory of relativity: deconstructing the term “data-limited” fisheries into components and guiding principles to support the science of fisheries management - Jason M. Cope; Natalie A. Dowling; Sybrand A. Hesp; Kristen L. Omori; Pia Bessell-Browne; Leandro Castello; Rowan Chick; Dawn Dougherty; Steven J. Holmes; Richard McGarvey; Daniel Ovando; Josh Nowlis; et al. (Reviews in Fish Biology and Fisheries, 2023)

A review of global fisheries for polychaete worms as a resource for recreational fishers: diversity, sustainability and research needs - Victoria J. Cole; Rowan C. Chick; Patricia A. Hutchings (Reviews in Fish Biology and Fisheries, 2018)